2015
DOI: 10.1590/1807-2577.1073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10% sodium bicarbonate on bond strength of enamel and dentin after bleaching with 38% hydrogen peroxide

Abstract: IntroductionBy-products of hydrogen peroxide degradation released during dental bleaching influence the polymerization of adhesive systems and composite resins, causing a reduction in shear bond strength to the tooth.Objectivethe aim of this article was to evaluate the effect of 10% sodium bicarbonate (SB), applied for different lengths of time, on the shear bond strength to enamel and dentin after bleaching.Material and methodEnamel and dentin blocks were divided into groups (n=10): (1) control: no bleaching;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Failure mode analysis demonstrated most adhesive type failures. This corroborates the findings of Darzé et al (2015), who also observed a predominance of adhesive failures in their studies, when using hydrogen peroxide.…”
Section: Discussionsupporting
confidence: 91%
“…Failure mode analysis demonstrated most adhesive type failures. This corroborates the findings of Darzé et al (2015), who also observed a predominance of adhesive failures in their studies, when using hydrogen peroxide.…”
Section: Discussionsupporting
confidence: 91%